E-Teaching Of Arabic To Non-Native Speakers In Pandemic/ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ù„Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨ØºÙŠØ±Ù‡Ø§ Ø¹Ù† Ø¨Ø¹Ø¯ ÙˆÙÙŠ Ø¹ØµØ± Ø§Ù†ØªØ´Ø§Ø± Ø§Ù„Ø§Ø¤Ø¨Ø¦Ø© - Khan, Lubna Farah; Mufidah, Nuril; Mohammad Idrees, Mohammad Umar Hafiz (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The article discusses modern media used during teaching Arabic to non-native speakers, especially e-learning which has become required in the new world, especially in the spread of infectious diseases. This situation urges the teaching system to switch to E-learning, which helps in studies, particularly during the lockdown period in the pandemic. It benefits the teaching by modern technologies and media in transmitting the language to learners. Learning Arabic has increased in recent times, and learners as a modern generation are using modern technologies to learn. This research on E-teaching of Arabic to non-native speakers in a pandemic is urgent, especially in the pandemic era. It must use media in teaching, especially in teaching Arabic. With the emergence of the Corona pandemic that has spread throughout the world, the demand raises high. The results were as following: use of media in education makes teaching more effective and integrated, give effective results, raises the competence of the teacher and the recipient of the language, increases attention and excitement among students, and develops the ability to teach with communication, and the media facilitate the education process even in the spread of diseases and does not interrupt the chain of education between the learner and the teacher. We arrived with results that the necessity of acquaintance with modern methods and technical means and using them will give fruitful results.